2013
DOI: 10.1016/j.adolescence.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of romantic stages and associations with problem behaviours during adolescence

Abstract: Normative romantic development is theorized to progress through a series of stages: affiliative activities, group‐based dating, and romantic relationships. The objectives of this research were threefold: empirically examine this progression of romantic stages during adolescence, determine normative and atypical trajectories, and examine links with internalizing and externalizing symptoms. An eight‐wave longitudinal study was conducted with 698 adolescents (53.6% female; Mage = 11.8 years at start of study). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 70 publications
7
63
2
1
Order By: Relevance
“…Although adolescents described relationships that were more serious than casual dating, there were issues with commitment, including concerns of exclusivity within these relationships. These findings are consistent with the developmental literature in that youth in middle adolescence engage in casual dating but that there is also a transformation at this stage when casual dating starts to take on the characteristics of committed relationships (Connolly et al 2004(Connolly et al , 2013Furman and Collins 2009). …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although adolescents described relationships that were more serious than casual dating, there were issues with commitment, including concerns of exclusivity within these relationships. These findings are consistent with the developmental literature in that youth in middle adolescence engage in casual dating but that there is also a transformation at this stage when casual dating starts to take on the characteristics of committed relationships (Connolly et al 2004(Connolly et al , 2013Furman and Collins 2009). …”
Section: Discussionsupporting
confidence: 88%
“…Next, it is helpful to examine the stages of dating and what developmental needs are met at each stage. Consistent with life course theory (Elder 1994), research by Connolly et al (2013) proposed that stages of adolescent dating depend on the age of the adolescent. In early adolescence, youth enter into romantic affiliations, which occur as same sex peer groups begin to transform into mixed sex peer groups.…”
Section: Introductionmentioning
confidence: 89%
“…For instance, several concurrent and retrospective studies revealed that most young adolescents have at least one current (and unreciprocated) other-sex crush and that the majority of older adolescents and young adults report having had at least one other-sex crush in their past , specifically during early adolescence, and before their first dates and romantic relationships (Bowker et al, 2012; Hearn, O’Sullivan, & Dudley, 2003; Hurlock & Klein, 1934; Kornreich, Hearn, Rodrigues, & O’Sullivan, 2003). These findings are consistent with theory and research on other-sex peer and romantic experiences indicating that young adolescents spend considerable time thinking about other-sex peers and romantic issues before actually interacting with or forming mutual heterosexual romantic relationships (e.g., Blyth, Hill, & Thiel, 1982; Connolly, Craig, Goldberg, & Pepler, 2004; Connolly, Nguyen, Pepler, Craig, & Jiang, 2013). There is also evidence that a small group of young adolescents (~25%), who are popular and physically attractive, come to receive the majority of crush nominations or are highly “crushed upon” (Bower et al, 2015; Bowker et al, 2012).…”
Section: Introductionsupporting
confidence: 89%
“…It is also critical for future work to understand the developmental stages in the formation of romantic relationships in adolescents with autism. That is, to the extent that these relationships exist, do they follow a similar developmental progression as in TD adolescent romantic relationships (i.e., mixed-gender group affiliations, then group dates, and eventually formation of romantic partnerships; Connolly, Nguyen, Pepler, Craig, & Jiang, 2013)? This approach may reveal critical information about the specific aspects of forming romantic and sexual partnerships in adolescence that are particularly difficult for adolescents with autism.…”
Section: Future Directions For Studying Adolescence As a Second Hit Fmentioning
confidence: 99%